Multidisciplinary Learning Using Online Networking in Biomedical Engineering - Shigehiro Hashimoto (Journal of Systemics, Cybernetics and Informatics)

(untitled)
Multifaceted thinking is important to tackle global issues for a sustainable society. It is difficult to select useful information from big data with one-sided thinking. This article takes as an example the controversy related to "vaccines" and "masks" in pandemics. Online education is useful to help control of infectious diseases. Face-to-face group meetings make it easy to interrupt group activities for individual activities. Online meetings are considering various ideas as an alternative to face-to-face meetings. The field of biomedical engineering includes faculties and students from diverse backgrounds. "Cross-cultural exchange" is also useful for multifaceted experiences. With the keyword "life support technology," a Japanese academic society and a Thai university conducted online networking for information exchange. The academic society is working to encourage students. The university is developing new fields. Information exchange is expected to lead to further developments in complex fields. It is expected to lead to the development of human resources that can deal with global problems.